Knowledge and attitude towards antibiotic use within consumers in Alkharj, Saudi Arabia - Saleh Abdullah Alqarni; Mohammed Abdulbari (Elsevier, 2019)
Background: The World Health Organization (WHO) has made the problem of solving antibiotic resistance one of its priorities. The present study was designed to determine knowledge and attitude towards antibiotic use in Alkharj, Saudi Arabia. Materials and methods: A cross-sectional survey was conducted in Alkharj, Saudi Arabia in the period of July 2017 to October 2017. A self-administered questionnaire included question on demographic characteristics, antibiotic usage, knowledge and attitude towards antibiotics use. The data were analyzed using Statistical Package For the Social Science (SPSS). Results: A total of 405 questionnaires were randomly distributed to the general public in Al-Kharj, Saudi Arabia. However, only 387 of the participants completed the questionnaire making the response rate 95.5%. The majority of the participants (64.3%) know antibiotics effective against bacterial infections while (46.8%) of participants believed that antibiotics can be used to treat viral infections. A significant positive correlation was noted between the respondents' antibiotic knowledge score and their attitude score (r = 0.523, p = 0.000). Significantly higher mean knowledge score of antibiotics was observed among study participants who were married, employed, participants working in health sector, high educational and high monthly income groups. Mean attitude score was found to be significantly high for females, participants working in health sector, high educational and high monthly income groups. Conclusion: The participants who have good knowledge towards antibiotics use showed positive attitude towards antibiotics use. Some specific groups should to be targeted for educational intervention in terms of appropriate antibiotic use, such as those who have received a low level of education and are in receipt of a low monthly income. Keywords: Knowledge, Attitude, Antibiotics use